Hemiarthroplasty and total hip arthroplasty in 30,830 patients with hip fractures: data from the Dutch Arthroplasty Register on revision and risk factors for revision - Moerman, Sophie (Acta Orthop, 2018)
Background and purpose — In the Netherlands about 40% of hip fractures are treated with a hemiarthroplasty (HA) or a total hip arthroplasty (THA). Although these procedures are claimed to have fewer complications than osteosynthesis (i.e., reoperation), complications still occur. Analyses of data from national registries with adequate completeness of revision surgery are important to establish guidelines to diminish the risk for revision. We identified risk factors for revision. Patients and methods — All patients older than 50 years of age with a hip fracture treated with arthroplasty by orthopedic surgeons and registered in the (national) Dutch arthroplasty register (LROI) were included in the study. In this register, patient characteristics and surgical details were prospectively collected. Revision surgery and reasons for revision were evaluated. A proportional hazard ratio model for revision was created using competing risk analysis (with death as competing risk). Results — 1-year revision rate of HA was (cumulative incidence function [CIF] 1.6% (95% CI 1.4–1.8) and THA 2.4% (CI 2.0–2.7). Dislocation was the most common reason for revision in both groups (HA 29%, THA 41%). Male sex, age under 80 years, posterolateral approach, and uncemented stem fixation were risk factors for revision in both THA and HA. THA patients with ASA classification III/IV were revised more often, whereas revision in the HA cohort was performed more often in ASA I/II patients. Interpretation — After arthroplasty of hip fractures, both a posterolateral approach and an uncemented hip stem have higher risks for revision surgery compared with an anterolateral approach and an cemented stem.